Impact of prosthetic rehabilitation on the life quality related to oral health in older adults - Zuilen Jiménez Quintana; Ileana Bárbara Grau León; Rafael Maresma Frómeta; Milay Justo Díaz; Emilio Terry Pérez (Medisur, 2021)
Background: Rehabilitation with dental prostheses is a solution that the vast majority of older adults use when faced with tooth loss, and its implications in the aesthetic, functional and psychological order. Objective: to evaluate the impact of prosthetic rehabilitation on the life quality related to oral health in older adults. Methods: descriptive study, carried out from January 2017 to December 2019, with patients who attended the prosthesis consultation at the Faculty of Stomatology (N =100), to receive prosthetic rehabilitation treatment. The Oral Health Impact Profile questionnaire was applied, and variables such as age, sex and the main reason for consultation were explored. Statistical significance tests were applied when comparing and correlating the study variables. Results: in the elderly rehabilitated with total prostheses, the female sex represented the 60% and the 77% requested attention due to aesthetic and functional concerns. Functional limitation, pain and physical disability were the most frequent problems. In terms of impact, 88 patients classified as “no impact”, which meant that prosthetic rehabilitation had a positive influence on perceived life quality. Conclusion: In most cases, prosthetic rehabilitation had a positive impact on the life quality related to oral health. Disability was not referring in any case.